Odpowiedzi

2009-11-12T16:33:34+01:00
A).
2x - 3y = 5
-x + 5y = 6

2x - 3y = 5
x = 5y - 6

2(5y - 6) - 3y = 5
10y - 12 - 3y = 5
7y = 17
y = 17/7


b).

3x - 3y + 3 = 0
x = 2 - 0,5y

3(2 - 0,5y) - 3y +3 = 0
6 - 1,5y - 3y +3 = 0
-4,5y = -9
y = 2

x = 2 - 0,5 * 2
x = 1
Najlepsza Odpowiedź!
2009-11-12T16:40:50+01:00
A.2x-3y=-5
-x+5y=6

2x-3y=-5
-x=6-5y/×-1

2x-3y=-5
x=-6+5y

2(-6+5y)-3y=-5
x=-6+5y

-12+10y-3y=-5
x=-6+5y

7y=7/7
x=-6+5y

y=1
x=-1

Spr.2x-3y=-5
2×(-1)-3×1=-5
-5=-5
L=P
-x+5y=6
-1×-1+5×1=6
6=6
L=P

B.3x-3y+3=0
x+0,5y-2=0

3x=3y-3/3
x+0,5y-2=0

x=y-1
x+0,5y-2=0

x=y-1
y-1+0,5y-2=0

x=y-1
1,5y=3-1,5

x=y-1
y=2

x=1
y=2

Spr.3x-3y+3=0
3×1-3×2+3=0
0=0
L=P
x+0,5y-2=0
1+0,5×2-2=0
0=0
L=P
2009-11-12T17:08:43+01:00
2x-3y=-5
-x+5y=6/(x-1)

x-5y=-6
x=5y-6
2(5y-6)-3y=-5
10y-12-3y=-5
7y=7/:7
y=1
-x+5razy1=6
-x=1/razy -1
x=-1

x=-1
y=1


3x-3y+3=0
x+0,5y-2=0

3x=3y-3
x=y-1
y-1+0,5y-2=0
1,5y=3/:1,5
y=2
3x-3razy2+3=0
3x=3/:3
x=1

x=1
y=2